Słowiańska krucjata Mickiewicza = The Slavic crusade of Mickiewicz - Ruszczyńska, Marta (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The author of the article attempts to describe selected elements of Mickiewicz's biography, as well as those fragments of his literary output which arrange themselves into a common tale of Slavdom. Among the selected texts there are the Paris talks, The composition of rules for the Polish Legion [Skład zasad legionu polskiego], Mickiewicz's speeches made to the inhabitants of Italian cities at the time of the Spring of Nations in 1848 and his travel letters. Reconstruction of Mickiewicz's activity at that time, accompanied by his Eastern mission of 1855, reveals his Slavophile tendencies flavored with millenarian attitude. Symbolic imagery rooted in an atmosphere of medieval crusades and the search for Slavic Jerusalem seems to have been close to the atmosphere of those events. In this perspective, the death of Mickiewicz in 1855 concluded and complemented his many years of efforts to restore the Slavs to history. As a result, the symbolic and mythical image of Mickiewicz's struggle for free Slavs found its way to the minds of the general public. However, for contemporary and subsequent interpreters, the literary events and the biographical facts seemed to be the most complementary tale from the life of the romantic poet.
Keywords: Mickiewicz, Adam (1798-1855); krucjata; słowianofilizm; historia; crusade; Slavdom; history